Zdravila za napredno zdravljenje - Švajger, Urban (Farmacevtski vestnik, 2022)
Advanced therapy medicinal products (ATMPs) comprise medicinal products based on cells, genes and tissue-engineered products that are rapidly gaining in importance in contemporary pharmaceutical and medical professions. While ATMPs have been a subject of focused and extensive basic and preclinical research within the most advanced research institutes worldwide in the last decades, in recent years, we are witnessing an increase in number of ATMPs that have gained marketing authorization both in the United States, as well as in member states of the EU. In development, manufacture, clinical translation and last but not least, regulation of ATMPs, the pharmaceutical profession is confronting numerous new challenges, which reflect several special features of this new generation of drugs. At the same time ATMPs are accompanied by a promising fact, that they represent a potential for the treatment of some of the most severe, previously incurable diseases, and a therapeutic approach that may significantly enhance patient's quality of life in the future.
Keywords: advanced therapy medi- cinal products; celična terapija; cell therapy; gene therapy; genska terapija; zdravila za napredna zdravljenja